StaTips Part V: The adjustment of the P value in the context of multiple comparisons - Giuseppe, Perinetti (South European Journal of Orthodontics and Dentofacial Research (SEJODR), 2018)
Very often researchers face the problem of multiple comparisons using the same data sets. When performing multiple comparisons,it happens that some P values below the desired cut-off level will be retrieved by chance, thus leading the researcher to havefalse positives. To reduce the risk of making wrong conclusions, statistical adjustment of the P values in the context of multiplecomparisons has been proposed over the last decades. This article will deal with two simple procedures, Bonferroni and Holm,commonly used in dental literature to adjust the P values in case of multiple comparisons.